EFFECT OF DEXTRIN AND LACTOSE IN PREPARATION OF POWDERS DOSAGE FORM FROM Centella asiatica EXTRACT - Saraswaty, Vienna; Risdian, Chandra; Mozef, Tjandrawati; S. Kardono, Leonardus Broto (LIPI Press, 2015)
Objective of this research is to investigate the influence of dextrin and lactose in preparation of dosage form from Centella asiatica (CA) ethanol extract. Powders dosage form of CA ethanol extract was prepared by kneading method. Previously, it had been known that to create CA extract concentrate long time is needed, i.e. more than 7 days. Drying preparation of CA extract by thin layer film in oven blower at 50oC gave a shorter drying time, i.e. 6 hours but it gave sticky form at the end of process. Preparation process to produce powders dosage by using dextrin and lactose was succesfully investigated in our laboratory. It resulted that dextrin was appropriate filler for preparation of CA extract powder. Powder dosage form of CA extract could be obtained after 6 hours of drying and using 30% w/w of dextrin (based on the weigh of wet extract at density of 1,000 gr.mL-1). Difference on amount of dextrin in CA extract gave influence on water content, acidity (pH), compressibility index, haussner ratio, flow propert,y and angle of repose significantly.